1997
DOI: 10.1007/s11606-006-5088-3
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Selective Serotonin Reuptake Inhibitors for the Management of Chronic Pain

Abstract: OBJECTIVE: To assess the effectiveness of selective serotonin reuptake inhibitors (SSRIs) in the management of chronic pain. METHODS:Randomized, controlled trials of SSRIs in the management of chronic pain were identified by searching MEDLINE from 1966 to 1997 and by contacting the manufacturers of SSRIs available in the United States.MAIN RESULTS: Nineteen studies were identified, including 10 on the treatment of headache, 3 on diabetic neuropathy, 3 on fibromyalgia, and 3 on mixed-chronic pain. SSRIs were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 24 publications
3
35
1
2
Order By: Relevance
“…Of 10 controlled trials examining SSRIs in the treatment of chronic headache, three found SSRIs to be no better than placebo and two found them to be marginally superior to placebo. In the remainder, there was some improvement but the analgesic effect was not superior to the comparison drug (82). There are three placebo-controlled trials using SSRIs in diabetic neuropathy; the larger study (n=46) found no difference between fluoxetine and placebo (83), while the two smaller studies found that paroxetine (84) and citalopram (85) exhibited some analgesic effect compared with placebo.…”
Section: Ssrismentioning
confidence: 99%
“…Of 10 controlled trials examining SSRIs in the treatment of chronic headache, three found SSRIs to be no better than placebo and two found them to be marginally superior to placebo. In the remainder, there was some improvement but the analgesic effect was not superior to the comparison drug (82). There are three placebo-controlled trials using SSRIs in diabetic neuropathy; the larger study (n=46) found no difference between fluoxetine and placebo (83), while the two smaller studies found that paroxetine (84) and citalopram (85) exhibited some analgesic effect compared with placebo.…”
Section: Ssrismentioning
confidence: 99%
“…Paroxetine is the most potent inhibitor of serotonin re-uptake among SSRIs (6,7). In clinical practice, paroxetine is used in the treatment of depressive disorders and as an adjuvant drug in chronic pain (2,6).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous open and controlled studies have shown that antidepressant drugs also have analgesic activity and particularly, selective serotonin reuptake inhibitors (SSRI) like Fluoxetine are effective in mixed, chronic pain [10] . It has also been shown that some antidepressants are superior to placebo in about 75% of studies [11] . A wide range of pain conditions are responsive to antidepressants, particularly diabetic neuropathy pain and probably rheumatoid arthritis [12] and migraine [13] , fibromyalgia [10] .…”
Section: Discussionmentioning
confidence: 99%